The Elephant’s Tail of VAPP, VDPV in the Polio End Game - Tiwari, Abhishek; Singh, Shivendra K; Manar, Manish; Bajpai, Prashant K (Indian Journal of Community Health, 2023)
A lot have been achieved by the Global Polio Eradication Initiative since 1988 after World Health Assembly passed the resolution to eradicate polio. Today, we have decreased the global polio incidence by 99.9% since GPEIs started working. We still have to remove polio from the few leftover pockets and get rid of the final 0.1% of polio cases. We have gained in positive terms that an estimated 16 million people today are walking and more than 1.5 million are alive because of the stakeholders’ strong, strategic and cooperative action. The journey to the last mile has some different difficulties and this article tries to provide additional insights into the strategies to achieve our goal of Polio eradication.